Post-bleaching patterns of Acanthaster planci, Culcita schmideliana, and Drupella spp. in coral nurseries and natural reefs, Kaafu Atoll, Maldives - Elias Bin Mohamad; Oriana Migliaccio (Journal of Marine Studies, 2025)
The 2024 mass coral bleaching event caused by prolonged thermal stress severely impacted numerous coral reef ecosystems across the Maldives, compromising structural complexity and recovery potential. Our study investigates the post-bleaching distribution, abundance, and ecological impact of key corallivorous species, Acanthaster planci, Culcita schmideliana, and Drupella spp., within two lagoon coral nurseries and a natural reef front in Kaafu Atoll, Maldives. Benthic surveys revealed varying degrees of coral loss due to bleaching. Live coral cover was lowest in lagoon coral nurseries (lowest, 14.2%) and highest at the reef front (34%). A. planci was absent from all transects, with only one individual sighted throughout the study. In contrast, C. schmideliana exhibited notable densities (up to 6 individuals/100 m²) on the reef crest and flat but was absent in lagoon nurseries. Drupella spp. were recorded at all sites, with highest densities and frequency of predation observed in Veli nursery (58%), where Acropora spp. were the most affected. Significant differences in snail size and aggregation intensity were found across the transects, with larger individuals on the reef front. The results suggest that while predators like A. planci remain rare post-bleaching, possibly due to the population control measures and thermal sensitivity, other underestimated predators such as Drupella spp. and C. schmideliana are exerting sustained pressure on recovering coral communities. Our findings highlight the need for targeted corallivore management in post-disturbance reef restoration strategies, particularly in coral nursery environments to support reef resilience and inform site-specific restoration strategies in nursery-based rehabilitation efforts.